Strategi Digital Branding Melalui Tiktok Dalam Meningkatkan Brand Awareness UMKM Mas Tolong Mas Surabaya (MTMSBY43) - Herdiansyah Herdiansyah; Istiono Istiono (Jurnal of Management and Social Sciences, 2026)
The development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize social media as the main instrument in building brand awareness. This study uses a qualitative descriptive approach with a field research type (field research). Data collection was carried out through observation, in-depth interviews with six sources (owner, financial manager, social media team, admin, crew, and customers), and documentation of the content of the TikTok account @mtm43surabaya. The results of the study show that: (1) MTMSBY43 implements a digital branding strategy with three main components, namely brand positioning as a social-based one-stop solution, a brand identity that focuses on a human-centered service approach, and a brand personality that reflects the character of local youth who are solution-oriented and socially concerned; (2) MTMSBY43 TikTok content is classified into three pillars, namely humanistic and realistic content (daily vlogs & live documentation), educational and transparent content (service portfolio), and humorous content (entertainment & engagement content) that builds high organic appeal; (3) TikTok acts as a primary growth driver for MTMSBY43's brand awareness through three mechanisms: creating brand recognition through the FYP algorithm, which reaches new audiences; driving brand recall through consistent uploads and a distinctive communication style; and building customer trust and brand loyalty through responsive two-way interactions